P27kip1 maintains a subset of leukemia stem cells in the quiescent state in murine MLL‐leukemia. Issue 6 (20th August 2013) - Zhang, Jun; Seet, Christopher S.; Sun, Clare; Li, Jing; You, Dewen; Volk, Andrew; Breslin, Peter; Li, Xingyu; Wei, Wei; Qian, Zhijian; Zeleznik-Le, Nancy J.; Zhang, Zhou; et al.
Abstract : MLL (mixed‐lineage leukemia)‐fusion genes induce the development of leukemia through deregulation of normal MLL target genes, such as HOXA9 and MEIS1. Both HOXA9 and MEIS1 are required for MLL‐fusion gene‐induced leukemogenesis. Co‐expression of HOXA9 and MEIS1 induces acute myeloid leukemia (AML) similar to that seen in mice in which MLL‐fusion genes are over‐expressed. p27kip1 (p27 hereafter), a negative regulator of the cell cycle, has also been defined as an MLL target, the expression of which is up‐regulated in MLL leukemic cells (LCs). To investigate whether p27 plays a role in the pathogenesis of MLL‐leukemia, we examined the effects of p27 deletion (p27−/−) on MLL‐AF9 (MA9)‐induced murine AML development. HOXA9/MEIS1 (H/M)‐induced, p27 wild‐type (p27+/+) and p27−/− AML were studied in parallel as controls. We found that LCs from both MA9‐AML and H/M‐AML can be separated into three fractions, a CD117‐CD11bhi differentiated fraction as well as CD117+CD11bhi and CD117+CD11blo, two less differentiated fractions. The CD117+CD11blo fraction, comprising only 1–3% of total LCs, expresses higher levels of early hematopoietic progenitor markers but lower levels of mature myeloid cell markers compared to other populations of LCs. p27 is expressed and is required for maintaining the quiescent and drug‐resistant states of the CD117+CD11blo fraction of MA9‐LCs but not of H/M‐LCs. p27 deletion significantly compromises the leukemogenic capacity of CD117+CD11blo MA9‐LCs by reducing the frequency of leukemic stem cells (LSCs) but does not do so in H/M‐LCs. In addition, we found that p27 is highly expressed and required for cell cycle arrest in the CD117‐CD11bhi fraction in both types of LCs. Furthermore, we found that c‐Myc expression is required for maintaining LCs in an undifferentiated state independently of proliferation. We concluded that p27 represses the proliferation of LCs, which is specifically required for maintaining the quiescent and drug‐resistant states of a small subset of MA9‐LSCs in collaboration with the differentiation blockage function of c‐Myc. Highlights: p27 is specifically expressed in a small subset of MLL‐AF9 LSC but not in HOXA9/MEIS1 LSC. The niche‐generated factors Flt3L and SCF induce p27 expression in MLL‐AF9 LSC but not in HOXA9/MEIS1 LSC. p27 restricts proliferation and maintains resistance to chemotherapeutic agents in MLL‐AF9 LSC. Over‐expression of p27 in HOXA9/MEIS1 LSC leads to quiescence and resistance to chemotherapeutic agents.